Penerapan Metode Ear Training Dalam Pembelajaran Paduan Suara SMP Negeri 1 Kudus - Kwidura, Nugroho; Haryono, Slamet; Raharjo, Eko Raharjo (Universitas Negeri Semarang, 2020)
The choir at SMP Negeri 1 Kudus is one of the extracurricular activities engaged in music. The obstacle faced by the choir members of SMP Negeri 1 Kudus is notation reading. The application of solfeggio ear training method is used by the instructors as a choir learning method in SMP Negeri 1 Kudus. The purpose of writing this study is to train the sensitivity of choir members in guessing the tone and reading the notation. This study uses a qualitative approach. Data collection techniques used are observation, interview, and documentation. Extracurricular teachers use steps in applying the method of solfeggio ear training on choir learning. The first step is to observe the members and give the song material. The second step, the instructors use imitating method (imitation) by writing song notation and applying it. The final step is to try by singing and changing the basic tone to train the member's sensitivity in guessing the tone.